Polyphonies coloniales - Caroline Déodat (Glad!)
As an integral part of the post-colonial national and heritage narrative of Mauritius, the Mauritian Sega is also part of another history, which is to be found in colonial narrative, but rather in an oral literature, in which the ability of performers of Sega to destabilize an essentialist conception of Mauritian creolity can still be heard. This article shows, on the one hand, a "macro" dimension relating to the ideologies of race, gender and colonialism that traverse the poetics of Sega, and on the other hand, a "micro" dimension of these linguistic practices of Sega. Thus, using the concept of polyphony is heuristic in order to show the irreducibly indexical dimension of this social practice — a poetic, musical and danced ritual — in that it refers to other discourses that have preceded it in history and belong to other enunciative times and spaces — i.e., the archives of the slavery and colonial period.